If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 12y = 20 Solving -4x + 12y = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12y' to each side of the equation. -4x + 12y + -12y = 20 + -12y Combine like terms: 12y + -12y = 0 -4x + 0 = 20 + -12y -4x = 20 + -12y Divide each side by '-4'. x = -5 + 3y Simplifying x = -5 + 3y
| X+55=0 | | 5x*x-32x+48=0 | | 3(5X+9)=26 | | 7y-5/2=8 | | Y+16=120 | | -9(y-86)=y+-48 | | x+1y+-z= | | 4(x+5)-3(2x+1)-8=6(x-10)+109 | | 10=2yx+4 | | 16x+4-4c=6(2x+1) | | y=(1/5)x-3 | | [w(5w^3)^-2]/w^-4 | | 5x-15=214.75 | | X(b+7)=12 | | 2/3(x)=4.6 | | mn+3p=7 | | 1/2x=145 | | 12-x=-5(x-4) | | 2/3(x)=3 | | 6x+10+2x-6=180 | | C=Wtc/1,000 | | 71+x+(z-5)+(y+21)=360 | | 1/2x=45 | | 4x-5+3x-3=90 | | x+2y-z= | | (x-5)(x+4)=22 | | X2=25/589 | | n^2+8n=-3 | | 6(8+n)=40+5n | | 2x-1y+32z= | | 11=-5-x | | 5x+4x(x-3)=(2x+6)(2x-6)+17x |